ROS related enzyme levels and its association to molecular signaling pathway in the development of head and neck cancer - Iplik, Elif Sinem; Ertugrul, Baris; Candan, Gonca; Pamuk, Saim; Aydemir, Levent; Celik, Mehmet; Ulusan, Murat; Ergen, Arzu; Cakmakoglu, Bedia (Cellular and Molecular Biology, 2018)
Given the prevalence and annual incidence of cancer, head and neck cancer is affecting more than 600,000 people each year. In this research, it was decided to investigate that which genes are involved and how MPO, NQO1, SOD2 enzyme levels effective to develop of head and neck cancer and for the first time at the tissue level. 35 tumor tissues in all head and neck anatomy and their surrounding tissue (70 in total) were enclosed the research that received surgery. Determination of the apoptosis genes expression levels (Mtch1, Akt1, Caspase3, Caspase9, Bcl2, Mdm2, mTOR) were determined by RT-PCR techniques and the same patients' sample used for ROS associated oxidant-antioxidant system by using MPO, NQO1, SOD2 enzyme levels using ELISA method. According to statistical results, caspase 9 gene was found statistically high expressed in early stage in contrast to late stage (p=0,013). Level of SOD2, NQO1 and MPO was determined and only MPO level was found significantly important on tumor tissues p=0,008).  Specially, our findings for high expression of Cas9 on early stage were thought to be the target for treatment with its well-known initiator role of the apoptosis. Our results suggest that the higher level of MPO in tumor tissues and indicates that it has some role on pathology of head and neck cancers. We believe that, our research will lead the proposal in-vivo studies and will open new areas on therapeutic targets.